ANALYSIS OF FACTORS CAUSING WORK FATIGUE IN MYGAS FILLING WORKERS AT PT. X, SOUTH TANGERANG CITY IN 2023 - Rizky Wulandari; Januar Ariyanto; Triana Srisantyorini; Dadang Herdiansyah (Muhammadiyah International Public Health and Medicine Proceeding, 2024)
Work fatigue is one of the occupational safety and health issues that must be addressed thoroughly because it can lead to a decrease in productivity and work performance. The World Health Organization (WHO) states that more than 414 work accidents occur every day in Indonesia, 27.8% are caused by significant fatigue, and around 9.5% or 39% of work accident victims are disabled. The purpose of this study is to find out the factors that cause work fatigue in PT. X mygas filling workers in the city of South Tangerang 2023, this research was carried out starting from January 28 with a cross-sectional design. The sample was taken with a total sampling technique of 38 respondents. The analysis was carried out bivariate through the chi-square test. With ethical number 10.063.B/KEPK-FKMUMJ/II/2023. As many as 39.6% of workers experienced moderate fatigue. The results of the bivariate test showed that there was a relationship between the age of 0.040 (p=0.05) and work fatigue in PT. X's mygas filling workers in the city of South Tangerang in 2023. And there was no relationship between gender 1,000 (p=0.05), working period 1,000 (0.05), work shift 0.571 (p=0.05) and sleep duration 0.305 (p=0.05) with work fatigue in mygas filling workers at PT. X. South Tangerang City 2023. It is expected to complete the work according to physical ability and capacity. Make the most of your rest time to recover from physical fatigue due to repetitive work.